Knowledge & Learning At The New Frontier: A Case Study In An Emerging Market - Griffiths, David A (Journal of Knowledge Management Practice, 2011)
This research is designed to assist practitioners and theorists in understanding the learning and knowledge challenges being faced by organisations as they expand their operations into new spaces in an attempt to seek out new or extend existing competitive advantage. To enable this process the paper conducts an exploratory case study in Quintiles (Asia Pacific), a United States pharmaceutical Clinical Research Organisation with a global presence. The narrative explores the drivers for expansion, but also uses the case study organisation to explore some of the issues that emerge when expanding operations into an emerging market. Prominence is given to intellectual capital and the supporting learning and knowledge functions within an organisation. The narrative also focuses on contextualising the environment, in this case the Asia Pacific region, particularly focusing on India and China, a key area of operation for the case study organisation. Using an evidence-based general model for knowledge management analysis, the paper sets out a case study method, which produces rich findings that reflect the issues set out in the literature surrounding the field. Findings are offered with recommendations for further research.